2012
DOI: 10.1177/1367493511424888
|View full text |Cite
|
Sign up to set email alerts
|

Using genograms to understand pediatric practices’ readiness for change to prevent abuse and neglect

Abstract: A novel use of genograms in primary care practice is to identify processes and relationships among physicians and staff prior to implementing practice change. The authors hypothesized that the genogram would inform researchers and practice staff, participating in a child maltreatment prevention study, how practice members function in a practice. They describe the use of genograms and show how the genogram results are associated with intervention uptake. Researchers constructed genograms, collected baseline sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In this project, we demonstrated that the PS bundles of tools and processes have multi-level effects on pediatric practice. In our previous studies, we found that the intervention enabled practices to understand their organizational dynamics and how these dynamics effect care to begin to make practice change (Abatemarco et al ., 2008; 2012). The current findings extend this previous work by showing that the intervention was effective in promoting the use of all three bundles of tools and processes to assess/screen, provide anticipatory guidance and resources to parents/caregivers, make referrals to community resources, and document follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this project, we demonstrated that the PS bundles of tools and processes have multi-level effects on pediatric practice. In our previous studies, we found that the intervention enabled practices to understand their organizational dynamics and how these dynamics effect care to begin to make practice change (Abatemarco et al ., 2008; 2012). The current findings extend this previous work by showing that the intervention was effective in promoting the use of all three bundles of tools and processes to assess/screen, provide anticipatory guidance and resources to parents/caregivers, make referrals to community resources, and document follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, child maltreatment assessment and safety prevention are often provided to families inconsistently or not at all depending on their personal characteristics (eg, race/ethnicity, socio-economic status). Use of universal and standardized screening/assessment, anticipatory guidance, referral, and follow-up tracking are strategies to provide equitable care to all patient populations (Schuster et al ., 2000; Abatemarco et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major events such as deaths, divorces, accidents, mental disorders, violence, chemical and alcohol dependence, and sexual abuse are also shown in this graphic representation, in order to plan for the full family health care 11 12 The familiarization of the pediatrician with this instrument increases the resoluteness of the service provided for the child, and it can also help the family to understand its members in new ways, as well as promote means to become partners in its own therapeutic plan 13 …”
Section: Introductionmentioning
confidence: 99%
“…Sustainable transformation relies on understanding practice culture and its effect on practice change, PCP perceptions and needs (Dempster et al , 2015), and the ‘buy-in’ of referring PCPs (Abatemarco et al , 2008; 2012). The present study aims to determine the referring PCPs’ most prevalent perceptions about the AP/Access Clinics as well as to characterize the influence of external factors.…”
Section: Introductionmentioning
confidence: 99%